Uwagi o formie przewidzianej dla celów dowodowych - Szpunar, Adam (Wydział Prawa i Administracji UAM, 1987)
The provisions on the form required for evidence purposes (ad probationem) belong to those which should be subject to critical evaluation in the course of works on the Civil Code reform. The article presents the history of the form ad probationem in Polish law, the form which is the manifestation of the French adage „lettres passent témoins". The said form was included into the Civil Code despite strong criticism. The author presents arguments for and against the said form. The present Art. 74 of the Civil Code provides for the moderate type of the form for evidence purposes. The interdiction to admit evidence in the form of witnesses or in the form of statements by the parties concerning the fact of concluding the transaction allows three exceptions: 1) if both sides express their consent in that respect, 2) if the fact of concluding the transaction is authenticated by means of a document, 3) if a court deems it necessary due to the particular circumstances of a case. The author analyses the above exception in detail, and reaches the conclusion that they mitigate the severity of the rule itself The author also discusses Art. 77 of the Civil Code which reads that if a contract was concluded in writing, its supplementation, change or dissolution by consent of both parties, as well as its renunciation, must be set down in writing. The author presents the views of the doctrine and the case law in that respect. The author criticizes Art. 75 of the Civil Code which requires the form for evidence purposes when a legal transaction contains a disposition of a right, the value of which exceeds 10 000 zloties, as well as when a legal transaction concerns an obligation to pay an amount exceeding 10 000 zloties. In the author's opinion, Art. 75 is a dead letter in practice. In conclusion the author does not put forth the postulate to eliminate the form ad probationem in its present shape. Yet, he is of the opinion that Art. 75 should be abrogated. Only in case of a loan exceeding 100 000 zloties should the contract be drawn up in writing.
Remarks on the from required for evidence purposes